Socio-Economic and Demographic Factors Affecting Access to Healthcare Services in Türkiye: A probit model analysis - Banu Beyaz Sipahi (Asia Pacific Journal of Health Management)
Background: Healthcare services aim to meet preventive and therapeutic needs and ensure equal access for all. Despite reforms like the Health Transformation Program in Türkiye, socio-economic and demographic inequalities in healthcare access persist. This study, based on the Grossman model, examines the factors affecting healthcare access in Türkiye.